South Asian religions : tradition and today - Pechilis, Karen; Raj, Selva J. (New York : Routledge, 2012)
'The religious landscape of south Asia is complex and fascinating. While existing literature tends to focus on the majority religions of Hinduism and Buddhism, much less attention is given to Jainism, Sikhism, Islam or Christianity. While not nelecting the majority traditions, this valuable resource also explores the important role which the minority traditions play in the religious life of the subcontinent, covering popular as well as elite expressions of religious faith. By examining the realities of religious life, and the ways in which the traditions are practised on the ground, this book provides an illuminating introduction to Asian religions'--
Keywords: South Asia -- Religion